Search without rescue? Evaluating the international search and rescue response to earthquake disasters - Anna Rom; Ilan Kelman (BMJ Global Health)
Earthquakes around the world are unnecessarily lethal and destructive, adversely affecting the health and well-being of affected populations. Most immediate deaths and injuries are caused by building collapse, making search and rescue (SAR) an early priority. In this review, we assess the SAR response to earthquake disasters. First, we review the evidence for the majority of individuals being rescued locally, often by relatives and neighbours. We then summarise evidence for successful live rescues by international SAR (ISAR) teams, along with the costs, ethics and other considerations of deployment. Finally, we propose an alternative approach to postdisaster ISAR, with the goal of reducing overall morbidity and mortality.